Ticagrelor and Eptifibatide Bolus Versus Ticagrelor and Eptifibatide Bolus With 2‐Hour Infusion in High‐Risk Acute Coronary Syndromes Patients Undergoing Early Percutaneous Coronary Intervention. Issue 6 (June 2017) - Marian, Moazez J.; Alli, Oluseun; Al Solaiman, Firas; Brott, Brigitta C.; Sasse, Mark; Leesar, Tara; Prabhu, Sumanth D.; Leesar, Massoud A.
Abstract : Background: In patients with non‐ST‐segment elevation acute coronary syndromes, inhibition of platelet aggregation (IPA) with a potent P2Y12 inhibitor, ticagrelor, was inferior to tirofiban infusion at 2 hours, indicating that glycoprotein IIb/IIIa inhibitors are still needed. Ticagrelor and eptifibatide bolus only may maximally inhibit platelet aggregation and decrease bleeding, but IPA with ticagrelor and eptifibatide bolus versus 2‐hour infusion is unknown. Methods and Results: A total of 70 P2Y12 ‐naïve patients, with high‐risk non‐ST‐segment elevation acute coronary syndromes, were randomized to ticagrelor and eptifibatide bolus (group 1) versus ticagrelor and eptifibatide bolus with 2‐hour infusion (group 2). Levels of IPA with ADP, thrombin receptor‐activating peptide, collagen, and high on‐treatment platelet reactivity were measured by light transmission aggregometry at baseline and at 2, 6, and 24 hours after percutaneous coronary intervention in both groups. The primary end point, IPA with ADP 20 μmol/L at 2 hours, was 99.59±0.43% in group 1 versus 99.88±1.0% in group 2 ( P <0.001 for noninferiority). High on‐treatment platelet reactivity with ADP was zero at 2, 6, and 24 hours in both groups. IPA levels with ADP, thrombin receptor‐activating peptide, and collagen were significantly higher at 2 and 6 hours than at 24 hours in both groups. Periprocedural myocardial infarction was not significantly different between the groups. Hemoglobin level was significantly less at 24 hours versus baseline in group 2 (13.35±1.8 versus 12.38±1.8 g/dL, respectively; P <0.01). Conclusions: Ticagrelor and eptifibatide bolus maximally inhibited platelet aggregation at 2 hours, which was associated with no significant hemoglobin drop after percutaneous coronary intervention. This obviates the need for eptifibatide 2‐hour infusion and might decrease bleeding complications. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01919723.